011 Gender differences in the effect of breast feeding on adult psychological well-being. (16th November 2010) - Cable, N; Bartley, M; McMunn, A; Kelly, Y
Abstract : Objective: To examine the changes in the social distribution of breast feeding and its effect on the psychological well-being of adults via the pathway of childhood psychological health. Design: Prospective cohort study. Setting: We used two British Birth Cohort Studies: National Child Developmental Study (NCDS, born in 1958) and 1970 British Birth Cohort Study (BCS70, born in 1970). Participants: Those who completed information on childhood data (breast feeding, mother's educational level, parenthood at birth, presence of older sibling, and psychosocial adjustment) and mid-adulthood (psychological ill health and self-efficacy) were included in this study (NCDS: N=7750; BCS70: N=6492). Main outcome measure: Childhood psychosocial adjustment was measured by the Bristol Social Adjustment Guides for the NCDS (collected at age 11) and the Rutter scale graded by a teacher for the BCS70 (collected at age 10). Adult psychological well-being (NCDS=age 33; BCS70=age 30) was indicated by psychological ill health and self-efficacy. Adult psychological ill health was indicated by the Malaise Inventory with a cutoff point of 7 or above. Self-efficacy was derived from the response to questions asking the study participants about their perceived level of control over their life. Methods: A dichotomised index of childhood adversity was created after tabulating information about parenthood, mother's age, mother's education, and presence of older siblings. The effect of breast feeding on childhood psychosocial adjustment and adult psychological well-being was examined using logistic regression. Men and women were analysed separately and the effects of breast feeding on the outcomes were adjusted for confounders. Results: Findings showed that the magnitude of the effect of breast feeding on adult psychological well-being is larger in women than in men. After accounting for the effect of childhood social adversity, breast feeding promoted psychosocial adjustment during childhood in girls in NCDS (OR 1.25, 95% CI 1.05 to 1.48) and in BCS70 (OR 1.44, 95% CI 1.15 to 1.81), but not in boys. In adulthood, being breast fed at birth was associated with higher self-efficacy (OR 1.31, 95% CI 1.06 to to 1.61) and lower risk of psychological ill health (OR 0.76, 95% CI 0.61 to to 0.96) in women in BCS70 only. However, no significant interaction effect was found between breast feeding and childhood social adversity. Conclusion: Although breast feeding did not moderate the negative effect of childhood social adversity on childhood or adulthood outcomes in this study, findings suggest that the practice of breast feeding can be important for women's psychological well-being throughout the lifecourse.